Perubahan jumlah sel purkinje cerebellum dan koordinasi motorik akibat pemberian alkohol pada tikus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Alcohol is a central nervous system depressant which had effect on cerebellum. The mechanism of alcohol-induced cerebellar damage possibly involves increase of the fluidity of cell membranes, hypoxia due to spasm of cerebral blood vessels, accumulation of toxic acetaldehyde, and nutritional deficiency. Objective: To reveal the effect of alcohol administration with different concentration on motor coordination disorder and the amount of Purkinje cells of adult male rats. Methods: Twenty four adult male rats (Fiattus norvegicus), with body weight range of 180-250 grams, were divided randomly into four groups. Group I, as control, was given aquadest 2 mUday. Each group II, Ill and IV were given alcohol 3%, 13%, and 24% 2 mUday, consecutively. Alcohol or aquadest was given orally during 30 days. After 30 days, motor coordination was assessed by measuring the survival of rats on rotarod with different speeds, 16, 24, and 32 rpm. And then, rats were decapitated and the brain was taken out for histological evaluation, paraffin method, and toloudine blue staining. Result: Motor coordination of alcohol groups with rotarod speed of 16 rpm, decreased significantly